2021
DOI: 10.3390/plants10040793
|View full text |Cite
|
Sign up to set email alerts
|

Differential Epigenetic Marks Are Associated with Apospory Expressivity in Diploid Hybrids of Paspalum rufum

Abstract: Apomixis seems to emerge from the deregulation of preexisting genes involved in sexuality by genetic and/or epigenetic mechanisms. The trait is associated with polyploidy, but diploid individuals of Paspalum rufum can form aposporous embryo sacs and develop clonal seeds. Moreover, diploid hybrid families presented a wide apospory expressivity variation. To locate methylation changes associated with apomixis expressivity, we compare relative DNA methylation levels, at CG, CHG, and CHH contexts, between full-sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 114 publications
(199 reference statements)
1
5
0
Order By: Relevance
“…FG has been reported. In contrast, the asynchronous pKNU:nlsYFP expression pattern in tgs1 ovules strongly recalls the developmental course of unreduced FGs in aposporous plants, which typically initiates during meiosis in Paspalum and Hieracium(Koltunow et al, 1998;Quarin et al, 2001;Soliman et al, 2021). In addition, our observations support the hypothesis of Jurani c et al…”
supporting
confidence: 87%
See 1 more Smart Citation
“…FG has been reported. In contrast, the asynchronous pKNU:nlsYFP expression pattern in tgs1 ovules strongly recalls the developmental course of unreduced FGs in aposporous plants, which typically initiates during meiosis in Paspalum and Hieracium(Koltunow et al, 1998;Quarin et al, 2001;Soliman et al, 2021). In addition, our observations support the hypothesis of Jurani c et al…”
supporting
confidence: 87%
“…However, although MMC‐like cells in mem and tex1 mutants can initiate gametophytic development without meiosis as revealed by the analysis of meiotic and gametophytic specific reporters (respectively, DMC1 immunolocalization in tex1 and pAKV:H2B‐YFP ), mem unreduced FGs abort development and no evidence for functional, mature tex1 FG has been reported. In contrast, the asynchronous pKNU:nlsYFP expression pattern in tgs1 ovules strongly recalls the developmental course of unreduced FGs in aposporous plants, which typically initiates during meiosis in Paspalum and Hieracium (Koltunow et al ., 1998; Quarin et al ., 2001; Soliman et al ., 2021). In addition, our observations support the hypothesis of Juranić et al .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we propose that the degree of apospory expressivity, in the diploid system of P. rufum , is transmitted to successive generations in a dose-dependent manner and could be modulated by genetic/epigenetic factors. Regarding the latter, a recent comparative study of epigenetic patterns between the F 1-C hybrids used as parental plants for F 2L versus those used for F 2H revealed that the differential apospory expressivity of these genotypes was associated with different methylation patterns [ 80 ]. Thus, our observations of the transgenerational transmission of apospory expressivity could be associated with the fact that in plants, epiallelic variation can be stably propagated over several generations [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few decades ago, apomixis was studied, mainly taking into account the genetic determination of the trait [ 59 , 113 ]. However, more recently, apomixis was approached from the epigenetic side since the trait was found to be more complex than was originally thought [ 114 , 115 , 116 ]. Several studies in E. curvula introduced new evidence of the epigenetic nature of some aspects of this particular reproductive mode.…”
Section: Epigenetics Regulation Of Apomixismentioning
confidence: 99%